Infection, inflammation, and risk of venous thromboembolism - Grimnes, Gro (UiT The Arctic University of Norway, 2018)
Paper IV is not available in Munin. Paper IV: Grimnes, G., Hindberg, K., Davids, M., Nieuwdorp, M., Mollnes, T.E., Brækkan. S.K., … Tichelaar, Y.I.G.V. A Vancomycin-induced shift of the gut microbiome in gram-negative direction increases plasma factor VIII:C levels: Results from a randomized, controlled trial. (Manuscript). SUMMARY Venous thromboembolism (VTE), including deep vein thrombosis and pulmonary embolism, is the third most common cardiovascular disease after myocardial infarction and stroke. The incidence of VTE is increasing and VTE contributes to a substantial burden of morbidity and mortality. To be able to prevent VTE in vulnerable subjects, there is a need for more knowledge about the pathophysiology and risk factors for VTE. Acute infection and several other inflammatory conditions have been associated with VTE risk in previous studies. The aim of the present thesis was to investigate the association between both short- and long-term inflammation and VTE risk. Further, the aim was to investigate the impact of acute infection on VTE risk in hospitalized patients, and, finally, whether gut microbiome composition was associated with systemic inflammation and coagulation. In Paper I, we used data from the fourth survey of the Tromsø Study, conducted in 1994-95, with follow-up until the end of 2012. Incident and recurrent VTE events were registered and thoroughly validated. Cox proportional hazards regression models were used to calculate hazard ratios for VTE across quartiles of the inflammatory marker neutrophil to lymphocyte ratio (NLR). We found no association between NLR measured at baseline in Tromsø 4 and future risk of incident or recurrent VTE. However, when restricting the follow-up time to the first three years after baseline, those with NLR above the 95th percentile had a 2.4-fold increased risk of VTE. In Papers II and III, we used a case-crossover designed study with the incident VTE cases from Tromsø 4 as the study population. We found that acute infection was a frequent and strong ...